2018
DOI: 10.3892/mmr.2018.8629
|View full text |Cite
|
Sign up to set email alerts
|

mTOR is involved in stroke-induced seizures and the anti-seizure effect of mild hypothermia

Abstract: Stroke is considered an underlying etiology of the development of seizures. Stroke leads to glucose and oxygen deficiency in neurons, resulting in brain dysfunction and injury. Mild hypothermia is a therapeutic strategy to inhibit stroke-induced seizures, which may be associated with the regulation of energy metabolism of the brain. Mammalian target of rapamycin (mTOR) signaling and solute carrier family 2, facilitated glucose transporter member (GLUT)-1 are critical for energy metabolism. Furthermore, mTOR ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
(45 reference statements)
1
5
0
Order By: Relevance
“…the decreased phosphorylation of p70S6K and RPS6) with CDH, the only known treatment that prevents lamellar structural failure experimentally and in clinical cases, further supports a role for this signalling in lamellar failure. A recent report demonstrating that therapeutic hypothermia in brain injury is effective via mTOR inhibition further supports the likelihood that CDH is effective in laminitis by blocking mTOR‐related signalling . Thus, the current data and research literature support a possible role of mTORC1/RPS6 signalling in lamellar failure in sepsis‐related laminitis.…”
Section: Discussionsupporting
confidence: 59%
“…the decreased phosphorylation of p70S6K and RPS6) with CDH, the only known treatment that prevents lamellar structural failure experimentally and in clinical cases, further supports a role for this signalling in lamellar failure. A recent report demonstrating that therapeutic hypothermia in brain injury is effective via mTOR inhibition further supports the likelihood that CDH is effective in laminitis by blocking mTOR‐related signalling . Thus, the current data and research literature support a possible role of mTORC1/RPS6 signalling in lamellar failure in sepsis‐related laminitis.…”
Section: Discussionsupporting
confidence: 59%
“…The results indicated that the expression of PI3K, Akt, mTOR were significantly higher than that of the Control group, suggesting that PI3K/Akt signaling pathway is involved in the epilepsy pathological process. The reasons are considered as follows: ①Excessive activation of mTOR can lead to gene expression of cerebral cortical malformation and the epileptic phenotype [24]; ②PI3K/Akt/mTOR signaling pathway participates in cell synthesis and proliferation and promotes the synthesis of microglia [25], thereby aggravating the immune inflammatory response and increasing inflammatory cell exudation.③PI3K/Akt/mTOR signal activates hypoxia-inducible factors and regulates the glucose transporter (GLUT), resulting in excessive activation of neurons [26]. Contrary to the postulated role of the PI3K/Akt/mTOR pathway in epilepsy pathology, there have been reports that this signaling cascade confers protective effects due to reducing neuronal apoptosis and ischemic brain injury [27].…”
Section: Discussionmentioning
confidence: 99%
“…Convulsive seizures occur along with an increased expression of phospho-mTOR and GLUT-1 in the cerebral cortex and hippocampus, as evidenced by immunohistochemistry and western blot analyses. Mild hypothermia and/or rapamycin treatment alleviates GCI-induced seizures by reducing the number of epileptic attacks, seizure severity scores, and seizure discharges [137]. This goes along with a reduction of phosphor-mTOR and its downstream effector p70S6 in neurons.…”
Section: Ischemic/hemorragic Stroke and Brain Traumamentioning
confidence: 94%
“…Stroke is also implicated in the etiology of seizures development. In rat models of global cerebral ischemia (GCI), during the first and the second days following GCI, convulsive seizures frequently occur, which are accompanied by seizure discharge shown by the EEG [137]. Convulsive seizures occur along with an increased expression of phospho-mTOR and GLUT-1 in the cerebral cortex and hippocampus, as evidenced by immunohistochemistry and western blot analyses.…”
Section: Ischemic/hemorragic Stroke and Brain Traumamentioning
confidence: 99%
See 1 more Smart Citation